Ekserimen Virtual Tourism 360° di Sumbawa: Dampak pada Persepsi Wisatawan dan Potensi Pembangunan Berkelanjutan - Firno Nino (Badan Penerbit STIEPARI Press, 2025)
This study analyzes the impact of 360° virtual tourism on tourist perceptions and the potential for sustainable development in Sumbawa Regency. Using a quasi-experimental method with 150 respondents, divided into experimental and control groups, data were collected through questionnaires and interviews. Analysis using independent t-tests and regression showed that the experimental group experienced a 35% increase in visit intention and a significant positive perception (p < 0.05) of Sumbawa tourist destinations. Virtual tourism also successfully built emotional connections with tourists and increased understanding of nature conservation. Virtual simulations have the potential to support sustainable development by reducing the environmental impact of physical visits and raising awareness of the importance of conservation. Mediation analysis showed that tourist perceptions mediated the relationship between virtual tourism and intention. This technology is recommended for integration into tourism marketing strategies to attract environmentally responsible tourists and support sustainable destination management.